ANALISIS FIQH JINAYAH TERHADAP JUAL BELI PETASAN - Hendra Gunawan MA (Institut agama islam negeri Padangsidimpuan, 2020)
Some people think that firecrackers are considered a fun game, especially on certain days including welcoming the turn of the year and even religious days including the month of Ramadan. Not only, it is fun for poison lovers but also a rain of sustenance for firecracker traders on certain days.But on the other hand, there have been many harms that have arisen due to firecrackers published in print and online news, ranging from injuries, fires, and even fatalities. Moving on from here, the author wishes to highlight the practice of buying and selling firecrackers which I will look at from the perspective of fiqh jinayah or the Islamic Criminal Law.The findings in this paper are that the sale and purchase of firecrackers is not only prohibited by legislation, but fiqh jinayah also prohibits the practice of buying and selling firecrackers due to 3 elements, namely; because there are elements of dharar (danger), tabdzir (wasting wealth), and doubts about the usefulness of firecrackers. For a more detailed explanation, read the discussion in this paper.